The Influence of person-organization Fit, Psychological Climate, and Work Stress on the Performance of Employees of the Public Works Department Bina Marga in East Java Province - Fatmasaria, Firianti; Sundjoto, Sundjoto; Rahayu, Sri (Gema Wiralodra, 2024)
This research investigates the complex dynamics of the Highways Public Works Department in East Java Province, exploring the multifaceted influence of Person-Organization Fit (POF), Psychological Climate, and Job Stress on employee performance. Person-Organization Fit, which reflects the alignment between individual values and organizational culture, is examined for its role in shaping employee effectiveness. This study assesses how the Psychological Climate in the workplace, which includes factors such as organizational culture and leadership style, contributes to employee well-being and performance. Additionally, the impact of Job Stress on employees in this particular public service context is also investigated. By analyzing these factors comprehensively, this research aims to provide actionable insights for organizational development and management strategy. This study uses a quantitative approach. The population in this study was all employees of the East Java Bina Marga DPU, totaling 667 people. The data collection method used in this research is by using a questionnaire. The data that has been collected is then tested using multiple linear regression analysis. These findings are expected to guide interventions that improve employee performance, job satisfaction, and overall organizational effectiveness. Because the Public Works Department plays an important role in infrastructure development, understanding and optimizing the factors that influence employee performance is important to ensure the successful implementation of public projects and services in East Java Province. This study contributes valuable knowledge at the intersection of organizational psychology and public administration, addressing practical implications for fostering conducive work environments and maximizing employee contributions. This research can be used as a basis for developing new theories or enriching existing theories regarding the influence of person-organization fit, psychological climate, and work stress on employee performance.